Connecting natural and cultural heritage practices. Is integration always a good idea? - Schlaman, Marjo J. (Ex Novo: Journal of Archaeology, 2019)
Integrated approaches in landscape management are often seen as the way forward to provide solutions for complex heritage problems that are related to policy, climate change, tourism, environmental planning and involving the public. This has led to a range of interdisciplinary and multidisciplinary projects aiming to add value to disciplinary approaches and gain new insights. Although interdisciplinarity is a promising research approach, there are many obstacles that may affect the quality of the project outcomes, slow down the overall organisation or create substantive errors. This raises therefore the question: is integration always a good idea? In this paper, I will show the complexity of cultural-historical landscapes and examine interdisciplinary approaches for their value as framework for historical landscapes. The role of historical assessments methods in landscape design is discussed. Finally, the example of two historical gardens and the process of their restoration and conservation will demonstrate how interdisciplinary and disciplinary approaches are related to each other in the garden design process.